2021
DOI: 10.21203/rs.3.rs-695957/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Galectin-1: a Potential Biomarker Differentiating Between Early Rheumatoid Arthritis and Spondyloarthritis

Abstract: Background: Galectin 1 (Gal1) is a lectin highly expressed in immune cells that plays a key immunoregulatory role in autoimmunity and resolution of chronic inflammation. Immune-mediated inflammatory diseases (IMIDs) are a broad group of disorders that share pathogenic mechanisms involving components of acquired and innate immunity. Although IMIDs can develop at onset similar features such as peripheral arthritis, they show differences in their evolution and response to treatments. Therefore, additional diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…o e er, many authors as Mart ne et al, 2020 reported that gal-1 can prevent agedependent autoimmunity indicating its important role in mediating tolerance. 1,33 In our study, we found a significant difference as regards serum gal-1 levels in RA group in comparison to PsA group and the control group. This agreed with Triguero-Martínez et al, 2022, 1 Mendez-Huergo et al, 2019 9 and Vilar et al, 2019, 34 as they reported that gal-1 level in RA patients was significantly increase compared to controls and PsA.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…o e er, many authors as Mart ne et al, 2020 reported that gal-1 can prevent agedependent autoimmunity indicating its important role in mediating tolerance. 1,33 In our study, we found a significant difference as regards serum gal-1 levels in RA group in comparison to PsA group and the control group. This agreed with Triguero-Martínez et al, 2022, 1 Mendez-Huergo et al, 2019 9 and Vilar et al, 2019, 34 as they reported that gal-1 level in RA patients was significantly increase compared to controls and PsA.…”
Section: Discussionsupporting
confidence: 47%
“…However, the systemic immune response is less marked in PsA which is not associated with elevation of inflammatory markers along with the absence of any specific autoantibodies which means that although PsA has autoinflammatory nature it is still lacking any evidence of autoimmune reactivity. Using new laboratory markers as gal-1, if proved useful, can be used in distinguishing between these two diseases aiming to decide the correct therapy for each of them 1,31,32 Therefore, this study aimed to determine the possibility of using gal-1 as a diagnostic marker to discriminate between RA and PsA with polyarthritis pattern, and between PsA and Ps, and to assess its relationship with disease activity and with skin lesion. The relation between age and sex in RA and gal-1 had been studied by many authors, as Triguero-Martínez, et al, 2022 1 who could not find a difference between patients and control group which agreed with our study finding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations